Pelatihan Penggunaan Pendekatan Etnometodologi Islam dalam Riset Akuntansi - Thalib, Mohamad Anwar (Penerbit Goodwood, 2023)
Purpose: This training aims to provide understanding to Sharia accounting students regarding the use of the Islamic ethnomethodology approach in accounting research Methodology/Approach: This training was carried out offline. There were 16 training participants. The participants were students majoring in Sharia accounting who are currently studying research. The participants were chosen because they were currently preparing a thesis proposal and the final assignment of the research The training was divided into three stages. The first is the presentation of material on Islamic ethnomethodology in the form of definitions, differences between Islamic ethnomethodology and modern ethnomethodology, and several examples of accounting studies using Islamic ethnomethodology. The second stage provides training on the use of Islamic ethno-methodology in accounting research. In this training, the participants were divided into groups, each consisting of two people. The third stage involved evaluating the participant worksheets. Results: The results of the training show that the training participants were able to apply Islamic ethnomethodological data analysis, including analysis of charity data, knowledge, faith, revealed information, and courtesy in accounting research. This was reflected in the results of the participants' worksheets, who were able to determine the points from the analysis of Islamic ethnomethodological data. Limitations: The limitation of this training is that the participants were only students majoring in Sharia accounting. Contribution: The contribution of the results of this training is to provide an understanding of how to use the Islamic ethno-methodology approach in accounting research.